Lupus and autoimmune shock: Use of intravenous gammaglobulin. Case report and proposal for a new designation - Hernández Bautista Victor Manuel; Stamatelos Albarrán Daniela; Vázquez García Rubén Ernesto (Instituto Nacional de Pediatría, 2014)
Shock is a state of hypotension and hypoperfusion which in turn leads to cellular dysfunction, neuroendocrine responses, inflam- matory mediator release, and alterations of the microcirculation. There are various ways of classifying tissue perfusion failure. A simple method is dividing them into a distributive category, such as septic or anaphylactic shock, and a non-distributive category such as hypovolemic shock. There is extensive knowledge on septic shock; the interaction between bacteria and the antigen presenting cell receptor (TRL-2, TRL-4) releases a proinflammatory cytokine storm, favoring the production of nitric oxide, thus perpetuating the hypotensive state. The imbalance between proinflammatory and anti-inflammatory cytokines creates an immunologic dysfunction, which favors the systemic inflammatory response syndrome and unleashes a shock state, a situation named immunologic disso- nance by Dr. Roger Bone in 1996. From our perspective, this term explains the alterations presented in one particular case, where the cornerstone is the dysfunction of the patient's immune system and its culmination in a distributive form of shock, which from our hypotheti- cal perspective is of autoimmune origin. We consider autoimmunity to be the platform leading to the state of immunologic dissonance responsible for autoimmune shock, which we believe merits a non-traditional approach. For this reason in a case in which we suspect shock based on autoimmunity, intravenous gammaglobulin was used in conjunction with a bolus of methylprednisolone in an attempt to counteract the immunologic dissonance; satisfactory results were obtained.